2020
DOI: 10.1136/annrheumdis-2020-217209
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of first-line tumour necrosis factor inhibitor versus non-tumour necrosis factor inhibitor biologics and targeted synthetic agents in patients with rheumatoid arthritis: results from a large US registry study

Abstract: ObjectivesThis study evaluated the comparative effectiveness of a tumour necrosis factor inhibitor (TNFi) versus a non-TNFi (biological disease-modifying antirheumatic drugs (bDMARDs) and targeted synthetic DMARDs (tsDMARDs)) as the first-line treatment following conventional synthetic DMARDs, as well as potential modifiers of response, observed in US clinical practice.MethodsData were from a large US healthcare registry (Consortium of Rheumatology Researchers of North America Rheumatoid Arthritis Registry). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 24 publications
(20 reference statements)
2
30
0
1
Order By: Relevance
“…Previous research did not show an effect of individual Disease Modifying Anti-Rheumatic Drugs (DMARDs) on fatigue. 14 However, to ensure our findings over time were not confounded by treatment, we repeated analyses over time in patients receiving initial methotrexate therapy since this was the most frequently occurring initial treatment (69%).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research did not show an effect of individual Disease Modifying Anti-Rheumatic Drugs (DMARDs) on fatigue. 14 However, to ensure our findings over time were not confounded by treatment, we repeated analyses over time in patients receiving initial methotrexate therapy since this was the most frequently occurring initial treatment (69%).…”
Section: Methodsmentioning
confidence: 99%
“…Response to 'Correspondence on 'Comparative effectiveness of first-line tumour necrosis factor inhibitor versus non-tumour necrosis factor inhibitor biologics and targeted synthetic agents in patients with rheumatoid arthritis: results from a large US registry study'' by Zheng et al We thank Zheng et al 1 for their interest in our study 2 and for providing constructive comments. They mention that even though the baseline mean Clinical Disease Activity Index (CDAI) was not statistically different, the proportion of patients with moderate or high disease at baseline was different and this could have been a key effect modifier.…”
mentioning
confidence: 99%
“…1 In our study, coexisting csDMARD use was considered only at baseline, but not during follow-up. 2 Prior csDMARD use was also evaluated. Changes in concurrent DMARD therapy over the follow-up period were not evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the article by Pappas et al 1 who evaluated the comparative effectiveness of a tumour necrosis factor inhibitor (TNFi) such as adalimumab, etanercept, certolizumab pegol, golimumab or infliximab versus a non-TNFi (abatacept, tocilizumab, rituximab, anakinra or tofacitinib) as the first-line treatment in patients with rheumatoid arthritis (RA). The authors concluded that there were no statistically significant differences observed between the TNFi and non-TNFi treatment groups for the outcomes assessed, including the Clinical Disease Activity Index (CDAI), the 28-Joint Modified Disease Activity Score, the Health Assessment Questionnaire Disability Index, EuroQol-5 Dimension score, morning stiffness and fatigue.…”
mentioning
confidence: 99%